BROCA APHASIA LANGUAGE IMPAIRMENT IN SARAH SCOTT’S YOUTUBE CHANNEL - Arswenda Dini Mulia; Rohmani Nur Indah (Universitas Putera Batam, 2021)
Aphasia is a language disorder caused by brain damage and makes the patient lose or impair language skills. One of the diseases which often cause people to experience aphasia is stroke. In this study, the researchers observed the characteristics of language impairment of Sarah Scott. She’s a young woman suffering from Broca's aphasia after stroke. This study employed a qualitative descriptive method on the utterances she produced in SymphUK YouTube channel as the data source. In collecting the data, the researchers watched and transcribed the utterances containing the language disorder. The analysis used the theory of Hallowel (2017) on the characteristics of Broca's aphasia and Ardila (2014) about the linguistics defects in aphasia. The finding shows that the most dominant characteristic was dysnomia, literal (phonemic) paraphasia, and agrammatism among twenty-six utterances. Then, the other characteristics that also appeared were disfluency, repetition, and telegraphic speech. Furthermore, the levels of language-impaired in Sarah Scott were morphemic, morphosyntactic, and phonetic. Thus, the following study should cover more subjects with different age, gender, and language to see whether more variation of characteristics of Broca's aphasia appears in different contexts.